THE EFFECT OF PROFITABILITY, UNDERWRITING RISK, AND REINSURANCE ON THE SOLVENCY OF LIFE INSURANCE COMPANY - Sekar Ayu Sukmarini; Bambang Soedaryono (Jurnal Ekonomi Trisakti, 2023)
This study aims to examine the effect of Profitability, Underwriting Risk, and Reinsurance on the Solvency of Life Insurance Companies. The sample used in this study uses life insurance companies registered by the Financial Services Authority(OJK) in the period 2017 to 2021. The number of samples used is 53 companies with 170 data observations. The sample method used in this study is purposive sampling, while the data analysis method used is multiple regression using the SPSS 25 program.The results of this study indicate that profitability has a positive and significant effect on the solvency of life insurance companies. Similarly, Underwriting Risk also has a positive and significant effect on the solvency of life insurance companies, while Reinsurance has a significant but negative effect on the solvency of life insurance companies in Indonesia.